2012
DOI: 10.1007/s00204-012-0800-z
|View full text |Cite
|
Sign up to set email alerts
|

Carcinogenicity of ortho-phenylenediamine dihydrochloride in rats and mice by two-year drinking water treatment

Abstract: The carcinogenicity of ortho-phenylenediamine (o-PD) was examined by administrating o-phenylenediamine dihydrochloride (o-PD2HCl) in dinking water to groups of 50 F344/DuCrj rats and 50 Crj:BDF₁ mice of both sexes for 2 years. The drinking water concentration of o-PD2HCl was 0, 500, 1,000 or 2,000 ppm (wt/wt) for male rats; 0, 250, 500 or 1,000 ppm for female rats; 0, 500, 1,000 or 2,000 ppm for male mice; and 0, 1,000, 2,000 or 4,000 ppm for female mice. Two-year administration of o-PD2HCl produced a dose-dep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…Whereas it should be noted that addition of OPD markedly increased the efficacy of ascorbate and EDTA, those combinations were not retained for the rest of the study due to the toxicity of OPD (Matsumoto et al, 2012).…”
Section: 3/ Effect Of Novel Molecule Associations On Co3o4p Dissolumentioning
confidence: 99%
“…Whereas it should be noted that addition of OPD markedly increased the efficacy of ascorbate and EDTA, those combinations were not retained for the rest of the study due to the toxicity of OPD (Matsumoto et al, 2012).…”
Section: 3/ Effect Of Novel Molecule Associations On Co3o4p Dissolumentioning
confidence: 99%
“…Therefore, numerous research studies have claimed that 1,2-DAB has mutagenic and carcinogenic effects in humans. 10,11 Besides this, 1,2-DAB is suspected as a serious environmental pollutant. On consideration of the health and environmental effects of 1,2-DAB, the American Conference of Governmental Industrial Hygienists (ACGIH) has declared 1,2-DAB carcinogenic and environmentally hazardous.…”
Section: Introductionmentioning
confidence: 99%
“… 82 , 85 , 86 On the contrary, some epidemiologic studies observed no evidence of a causal association between occupational exposure to hair dyes and the increased risk for bladder cancer among male hairdressers. 87 , 88 Permanent hair dyes may contain o -phenylenediamine 89 29 and 4-chloro- o -phenylenediamine 30 ( Figure 1 ), 90 which have shown carcinogenicity in animal studies. These chemicals can lead to the formation of 8-oxo-7,8-dihydro-2′-deoxyguanosine (8-oxodG) that is a marker of oxidative stress.…”
Section: Association Between Hair Dye Use and Cancermentioning
confidence: 99%
“…Hair dyes contain arylamines; therefore, hairdressers and barbers are at risk of cancer from occupational exposure to arylamines. Findings demonstrate that individuals who pursue these occupations, particularly for longer than 10 years, experience a significantly increased risk of bladder cancer. ,, On the contrary, some epidemiologic studies observed no evidence of a causal association between occupational exposure to hair dyes and the increased risk for bladder cancer among male hairdressers. , Permanent hair dyes may contain o -phenylenediamine 29 and 4-chloro- o -phenylenediamine 30 (Figure ), which have shown carcinogenicity in animal studies. These chemicals can lead to the formation of 8-oxo-7,8-dihydro-2′-deoxyguanosine (8-oxodG) that is a marker of oxidative stress .…”
Section: Association Between Hair Dye Use and Cancermentioning
confidence: 99%